Dataset for "Traffic intensity and vegetation management affect flower-visiting insects and their response to resources in road verges" - Horstmann, Svenja; Auffret, Alistair G.; Herbertsson, Lina; Klatt, Björn K.; Müller, Sophie; Öckinger, Erik (Swedish University of Agricultural Sciences, 2024)
This data set comprises the flower density and abundance, richness and evenness of wild bees and butterflies in 37 road verges in Skåne county in southern Sweden, as well as information about the respective road verge width, traffic intensity in the adjacent road, mowing frequency, habitat quality and exact location.
It is a crossed study design, allowing to separate the effects of road verge classification (valuable or regular) from the effects of mowing frequency (mowing once or twice) through the following four combinations: Valuable and mowed once, valuable and mowed twice, regular and mowed twice, regular and mowed once. Within each combination, there is a gradient in traffic intensity comparable between combinations.
The data on plants and pollinators was assessed during fieldwork in 2021 and 2022. The data on traffic intensity and habitat quality was derived from the national road database: https://nvdb2012.trafikverket.se/.

To get information about land cover we used the National Land Cover Database from the Swedish Environmental Protection Agency:
https://metadatakatalogen.naturvardsverket.se/metadatakatalogen/GetMetaDataById?id=8853721d-a466-4c01-afcc-9eae57b17b39
To select landscapes without meadows and pastures of high nature value within 350m of the study sites we used the TUVA database from the Swedish Board of Agriculture:
https://etjanst.sjv.se/tuvaut/
To select road verges, we used the environmental and infrastructure data from the national road database NVDB from Trafikverket:
https://nvdb2012.trafikverket.se/

The data set consists of 37 rows and 361 columns, excluding headers. Each row contains information for one studied road verge (37 in total). The columns contain information on the unique identifier of each road verge (‘SiteID’), the coordinates of the middle of the 200 m long transect in each road verge (‘N’, ‘E’), road verge quality (‘RV_Quality’), mowing frequency (‘Mowed’), mean width of the road verge (‘VergeWidthMean’), traffic intensity (‘TI’), flower density (‘Flow_Dens’), butterfly abundance, richness and evenness (‘BF_Abun’, ‘BF_Rich’, ‘BF_Even’), wild bee abundance, richness and evenness (‘WB_Abun’, ‘WB_Rich’, ‘WB_Even’), and vascular plant richness (‘Vasc_Rich’). The columns P-IN contain the frequency of each vascular plant species observed in our study, with the species name as column header. The columns IO-JU contain the abundance of butterfly species observed in our study, with the species name as column header. The columns JV-MW contain the abundance of wild bee species observed in our study, with the species name as column header.
For further explanation on the information and how it was assessed, please see the README file.

Dessa data beskriver artrikedom av växter, dagfjärilar och vilda bin i vägkanter. Se engelsk beskrivning för mer detaljerad information.
Datamängden består av 37 rader och 361 kolumner, exklusive rubriker. Varje rad innehåller information om en studerad vägkanter (totalt 37). Se den engelska beskrivningen och README för en beskrivning av informationen i varje kolumn.
Dataset för "Trafikintensitet och vegetationsskötsel påverkar blombesökande insekter och deras respons på resurser i vägkanter"
Keywords: butterflies; species richness; species abundance; road verges; vägrenar; traffic; trafik; Hymenoptera; steklar; road traffic; vägtrafik; roads; vägar; mowing; slåtter; vascular plants; kärlväxter; flowers (plants); blommor (växter); tracheophyta; hymenoptera; lepidoptera; Ecology; Ekologi